A stronghold of strong medicine: place attachment and the South Unit, Badlands National Park - Bills, Amanda M., author; Sherman, Kathleen Pickering, advisor; Browne, Katherine E., committee member; Fiege, Mark, committee member (Colorado State University. Libraries, 2013)
This thesis explores the relationship between the Oglala Sioux Tribe and the White River Badlands of South Dakota. Through constant interaction the Oglala Lakota have built a place attachment to these badlands located on the South Unit of Badlands National Park. Described through qualitative interviews, the contentious past of the South Unit colors this attachment, but the possibility of creating a new park on the South Unit offers the Oglala Sioux Tribe the unique opportunity to re-create a sense of place for the youth of the Reservation that is not based on a history of dispossession but rather on the precedent-setting repossession of national park land through the creation of the first Tribal National Park in the United States.
Keywords: Badlands National Park; National Park Service; Oglala Sioux Tribe; place attachment; South Unit; Tribal National Park